Fundamental concepts and methodologies in evaluatology - Jianfeng Zhan (BenchCouncil Transactions on Benchmarks, Standards and Evaluations)
While I have authored three articles introducing Evaluatology, a novel discipline that encompasses the science and engineering of evaluation across various domains, I have struggled to fully depict this challenging yet promising field.This article delves into the fundamental concepts and methodologies within Evaluatology. I aim to provide a complete picture of evaluation problems in Evaluatology based on my proposed fundamental methodology of understanding a thing. In diverse engineering fields, testbeds, experimental platforms, or simulation environments are commonly utilized to evaluate design or implementation decisions. However, a rigorous methodology is often lacking. I propose a rigorous methodology rooted in Evaluatology for testbeds, experimental platforms, or simulation environments.